2020
DOI: 10.1021/acs.langmuir.0c00804
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Mammalian-Cell Membranes on Bioelectronic Devices with Functional Transmembrane Proteins

Abstract: Transmembrane proteins (TMPs) regulate processes occurring at the cell surface and are essential gatekeepers of information flow across the membrane. TMPs are difficult to study, given the complex environment of the membrane and its influence on protein conformation, mobility, biomolecule interaction, and activity. For the first time, we create mammalian biomembranes supported on a transparent, electrically conducting polymer surface, which enables dual electrical and optical monitoring of TMP function in its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
100
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(107 citation statements)
references
References 35 publications
6
100
1
Order By: Relevance
“… 26 Work by Daniels and Owens has shown that the assembly of SLBs on organic conductive polymers such as PEDOT:PSS, 23 along with the coupling of this material to organic electrochemical transistors (OECTs), can generate a sensor to enable monitoring of pathogen–host interactions that maintains native-like protein mobility and excellent electronic properties (Figure 2 ). 22 , 27 This recent progress in the development of biomimetic interfaces has led to fundamental insights into the structure and function of viruses such as Influenza 28 and the herpes simplex virus (HSV), 29 and could be used to provide similar insights in viruses such as SARS-CoV-2. These platforms have also been used as bioanalytical tools for antiviral drug studies.…”
Section: Studying Emerging Pathogens Electrochemicallymentioning
confidence: 99%
See 1 more Smart Citation
“… 26 Work by Daniels and Owens has shown that the assembly of SLBs on organic conductive polymers such as PEDOT:PSS, 23 along with the coupling of this material to organic electrochemical transistors (OECTs), can generate a sensor to enable monitoring of pathogen–host interactions that maintains native-like protein mobility and excellent electronic properties (Figure 2 ). 22 , 27 This recent progress in the development of biomimetic interfaces has led to fundamental insights into the structure and function of viruses such as Influenza 28 and the herpes simplex virus (HSV), 29 and could be used to provide similar insights in viruses such as SARS-CoV-2. These platforms have also been used as bioanalytical tools for antiviral drug studies.…”
Section: Studying Emerging Pathogens Electrochemicallymentioning
confidence: 99%
“… SLB type Detection Shortcoming Ref. Solvent-assisted lipid bilayer formation Protein diffusion in membrane Overly simplified model due to lack of native protein incorporation in the membrane 15 , 16 Protein delivery into SLB via cell bleb on mica, silicon dioxide, glass Allows for study of proteins whose fluidity, orientation, and function has been better preserved Substrates are electrically insulating and rigid, thereby hindering the insertion, function, and mobility of transmembrane proteins 17 23 Protein delivery into SLB via cell bleb on conductive polymers such as PEDOT:PSS Allows for detection of pathogen–host interactions that preserve native-like protein mobility and superior electronic properties n/a 22 , 23 , 27 – 31 …”
Section: Studying Emerging Pathogens Electrochemicallymentioning
confidence: 99%
“…One approach to introducing physiologically relevant features into SLBs is the reconstitution of purified membrane proteins into proteoliposomes and the subsequent formation of SLBs from these proteoliposomes. This method has been used in several studies including the study of proteinprotein interactions 1 , membrane-protein interactions and membrane remodelling [2][3][4] , membrane poration 5 , host-pathogen interactions 6 and single receptor activation 7 among others.…”
Section: Mainmentioning
confidence: 99%
“…[ 18–23 ] In addition, a recent research direction explores interfacing supported lipid bilayers (SLBs) with a conductive film based on conjugated polymers with promising results. [ 24–29 ] Thus, we present a brief overview on the origin of the electronic and optical properties of these polymers.…”
Section: Overview Of Conjugated Polymers and Liposomesmentioning
confidence: 99%
“…A promising new approach that further demonstrates the utility of interfacing conjugated polymers with liposomes is investigating SLBs supported by the conjugated polymer when used as an active channel in an organic electrochemical transistor. [ 24–28,54,55 ] Here, the conjugated polymer establishes an electronic communication with the membrane and is an electric read‐out, revealing changes in the permeability and morphology of the SLB. This is a promising platform shown to identify bacterial toxins or antibiotic targets that disrupt bacteria, [ 27 ] elucidate the interaction of compounds [ 26 ] and insertion of proteins with the membrane, [ 25 ] monitor ion channel activity in complex biological SLBs [ 28 ] and in SLBs incorporating gramicidin channel.…”
Section: Applications Of Conjugated Polymer/polyelectrolytes‐liposomementioning
confidence: 99%